2014
DOI: 10.1002/ijc.29292
|View full text |Cite
|
Sign up to set email alerts
|

Type II diabetes mellitus is associated with a reduced risk of cholangiocarcinoma in patients with biliary tract diseases

Abstract: Ithas not yet been reported whether Type II diabetes mellitus (DM) is associated with an increased cholangiocarcinoma (CC) risk in patients with biliary tract diseases. We identified 123,050 patients concomitantly diagnosed with biliary tract diseases and DM between 1998 and 2010. The control cohort consisted of 122,721 individuals with biliary tract diseases but not DM. Both cohorts were followed-up until the end of 2010 to estimate the risk of CC. We also compared the risk of CC between DM and non-DM cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…Although previous studies have shown that DM is a risk factor for ICC , the prevalence of DM did not differ between the ICC group and the control group in the present study. However, almost all the patients in the control group had MLT from colorectal cancer, which has also been reported to be associated with DM .…”
Section: Discussioncontrasting
confidence: 98%
“…Although previous studies have shown that DM is a risk factor for ICC , the prevalence of DM did not differ between the ICC group and the control group in the present study. However, almost all the patients in the control group had MLT from colorectal cancer, which has also been reported to be associated with DM .…”
Section: Discussioncontrasting
confidence: 98%
“…One study in a non-endemic area for liver-fluke infection reported that DM may be a protective factor against CCA development in those with biliary tract diseases. However, DM was also associated with significantly increased risk of CCA in patients without these conditions [ 14 ]. This finding is consistent with another study in northeastern Thailand, which found that, before praziquantel (PQZ) treatment, O .…”
Section: Discussionmentioning
confidence: 99%
“…viverrini is not the only risk factor for CCA. Several other diseases have been linked with the condition, including diabetes mellitus (DM) [ 13 , 14 ]. Recent studies have reported that DM is a risk factor for both intrahepatic and extrahepatic subtypes of CCA [ 15 ]: patients with DM were 1.6 times more likely to be incident cases of CCA compared with those without DM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As genes encoding proteins related to insulin receptor, IGF1R could stimulate renal cancer cells [28]. Type II diabetes mellitus could reduce the risk of cholangiocarcinoma in patients with biliary tract diseases [29].…”
Section: Discussionmentioning
confidence: 99%